2014
DOI: 10.1186/1477-3155-12-16
|View full text |Cite
|
Sign up to set email alerts
|

Carbon and fullerene nanomaterials in plant system

Abstract: Both the functionalized and non functionalized carbon nanomaterials influence fruit and crop production in edible plants and vegetables. The fullerene, C60 and carbon nanotubes have been shown to increase the water retaining capacity, biomass and fruit yield in plants up to ~118% which is a remarkable achievement of nanotechnology in recent years. The fullerene treated bitter melon seeds also increase the phytomedicine contents such as cucurbitacin-B (74%), lycopene (82%), charantin (20%) and insulin (91%). Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
114
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 257 publications
(120 citation statements)
references
References 69 publications
2
114
1
3
Order By: Relevance
“…To investigate the uptake, transport, and distribution of nanoparticles in plants, and the impact of nanomaterials on plant function, the first key step is to deliver the nanoparticles into plants in vivo [45]. Uptake and accumulation of carbon nanotubes along with fullerenes and fullerol in edible and crop plants were previously reported [46]. The penetration of CNTs into the plant system is inversely proportional to its size.…”
Section: N-cds' Insertion Into Leaf Cellsmentioning
confidence: 99%
“…To investigate the uptake, transport, and distribution of nanoparticles in plants, and the impact of nanomaterials on plant function, the first key step is to deliver the nanoparticles into plants in vivo [45]. Uptake and accumulation of carbon nanotubes along with fullerenes and fullerol in edible and crop plants were previously reported [46]. The penetration of CNTs into the plant system is inversely proportional to its size.…”
Section: N-cds' Insertion Into Leaf Cellsmentioning
confidence: 99%
“…The effect of carbon nanomaterials of varying sizes and concentrations on different parts of a variety of plants has been studied [44,46,148,166,177-182]. Multi-walled carbon nanotubes (MWCNTs) enhanced alfalfa and wheat germination and root elongation, but the particle uptake and translocation was insignificant [183].…”
Section: Reviewmentioning
confidence: 99%
“…Recent reviews have addressed toxic and stimulating NP effects, summarized NP concentrations found in plants, and discussed how plants are exposed to NPs in soil, water and air (Gardea-Torresdey et al, 2003;Handy et al, 2008a;Husen & Siddiqi, 2014;Jackson et al, 2013;Klaine et al, 2008;Ma et al, 2010a;Miralles et al, 2012a;Navarro et al, 2008;von Moos et al, 2014). Central, not recently systematically addressed topics are the actual barriers, pathways and transport processes that NPs face in plants.…”
Section: Introductionmentioning
confidence: 98%